2020
DOI: 10.6004/jnccn.2020.7570
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Danish Patients With Glioma and a Cancer-Free Comparison Group

Abstract: Background: It is well established that patients with glioma may experience adverse general (eg, headache) or focal symptoms (eg, personality changes) and neurocognitive deficits (eg, planning), but they may also experience severe emotional distress. We investigated the prevalence of depressive symptoms in patients with newly diagnosed glioma and in matched cancer-free persons. Methods: For this study, we recruited patients with glioma diagnosed within 12 months at all 4 neurosurgical clinics in Denmark. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
7
2
Order By: Relevance
“…In a study by Hao et al [ 22 ] evaluating depression in 190 consecutive patients with gliomas, HADS revealed that education < 12 years, female sex, marital status (single/divorced/widowed/married), and chronic kidney disease were independent risk factors for depression, while the Zung self-rating depression scale revealed that female sex, marital status (single/divorced/widowed/married), and hyperlipidemia were independent risk factors for depression [ 22 ]. In a study involving 363 patients with gliomas (response rate, 66%) and 481 cancer-free patients (response rate, 37%) diagnosed within 12 months at neurosurgery clinics in Denmark, the prevalence of depression did not differ significantly by sex, age, tumor grade, marital status, or education level, inconsistent with previous findings [ 49 ]. The study was limited in that antidepressant use in the follow-up period was not investigated, possibly underestimating the prevalence of moderate-to-severe depression, and patients with significant cognitive impairment were excluded, possibly deceasing the generalizability of the results to the entire population with depression [ 49 ].…”
Section: Depression and Risk Factors In Gliomacontrasting
confidence: 60%
See 1 more Smart Citation
“…In a study by Hao et al [ 22 ] evaluating depression in 190 consecutive patients with gliomas, HADS revealed that education < 12 years, female sex, marital status (single/divorced/widowed/married), and chronic kidney disease were independent risk factors for depression, while the Zung self-rating depression scale revealed that female sex, marital status (single/divorced/widowed/married), and hyperlipidemia were independent risk factors for depression [ 22 ]. In a study involving 363 patients with gliomas (response rate, 66%) and 481 cancer-free patients (response rate, 37%) diagnosed within 12 months at neurosurgery clinics in Denmark, the prevalence of depression did not differ significantly by sex, age, tumor grade, marital status, or education level, inconsistent with previous findings [ 49 ]. The study was limited in that antidepressant use in the follow-up period was not investigated, possibly underestimating the prevalence of moderate-to-severe depression, and patients with significant cognitive impairment were excluded, possibly deceasing the generalizability of the results to the entire population with depression [ 49 ].…”
Section: Depression and Risk Factors In Gliomacontrasting
confidence: 60%
“…In a study involving 363 patients with gliomas (response rate, 66%) and 481 cancer-free patients (response rate, 37%) diagnosed within 12 months at neurosurgery clinics in Denmark, the prevalence of depression did not differ significantly by sex, age, tumor grade, marital status, or education level, inconsistent with previous findings [ 49 ]. The study was limited in that antidepressant use in the follow-up period was not investigated, possibly underestimating the prevalence of moderate-to-severe depression, and patients with significant cognitive impairment were excluded, possibly deceasing the generalizability of the results to the entire population with depression [ 49 ].…”
Section: Depression and Risk Factors In Gliomacontrasting
confidence: 60%
“…For chronic mental disorders, it has already been reported that major depressive disorder [ 50 ], anorexia [ 77 ], Parkinson’s disease [ 78 ], anxiety disease [ 79 ], and addiction disease [ 80 ] are associated with poorer mental health and more mental health problems. Likewise, it was already reported that somatic disease events intensified mental health problems (myocardial infarction [ 81 ], stroke [ 82 ], cancer [ 83 ], and thrombosis [ 84 ]). In terms of practical implications, the present results indicated that the onset of chronic mental disorder led to an increase of 2.1 CES-D points, while the experience of a somatic disease event led to an increase of 1.46 CES-D points.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, antidepressants were used in 8.4%, 9.9% and 13.6% of patients, respectively. Published studies reported a prevalence of depression among patients with glioma ranging from 15% to 93% 27‐30 . There is a significant difference between self‐reported and physician‐reported prevalence of depression in glioma patients as shown in a systematic review of observational studies 31 …”
Section: Discussionmentioning
confidence: 99%